Arts as performance - Davies, David -1937 (Malden Blackwell, 2004)
In this richly argued and provocative book, David Davies elaborates and defends a broad conceptual framework for thinking about the arts that reveals important continuities and discontinuities between traditional and modern art, and between different artistic disciplines. Elaborates and defends a broad conceptual framework for thinking about the arts.Offers a provocative view about the kinds of things that artworks are and how they are to be understood.Reveals important continuities and discontinuities between traditional and modern art.Highlights core topics in aesthetics and art theory, including traditional theories about the nature of art, aesthetic appreciation, artistic intentions, performance, and artistic meaning.